Successful aging and subjective aging: toward a framework to research a neglected connection - Sabatini, Serena; Rupprecht, Fiona; Kaspar, Roman; Klusmann, Verena; Kornadt, Anna Elena; Nikitin, Jana; Schönstein, Anton; Stephan, Yannick; Wettstein, Markus; Wurm, Susanne; Diehl, Manfred; Wahl, Hans-Werner (The gerontologist, 2025)
Research related to subjective aging, which describes how individuals perceive, interpret, and evaluate their own aging, has substantially grown in the past 2 decades. Evidence from longitudinal studies shows that subjective aging predicts health, quality of life, and functioning in later life. However, the existing literature on successful aging has mostly neglected the role of subjective aging. This paper proposes an extended framework of successful aging linking subjective aging conceptually and empirically to Rowe and Kahn’s ((1997). Successful aging. Gerontologist, 37(4), 433-440) 3 original key criteria of successful aging (i.e., avoiding disease and disability, maintaining high cognitive and physical function, and engagement with life). A particular focus is placed on subjective aging as an antecedent of successful aging. A review of the empirical subjective aging literature shows that subjective aging concepts consistently predict all 3 of Rowe and Kahn’s criteria of successful aging. Mechanisms underlying these relations are discussed at 3 levels, namely psychological, behavioral, and physiological pathways. The proposed addition also takes into consideration the interconnections between subjective aging and successful aging throughout the life span and across historical time. Finally, we discuss the importance of facilitating successful aging through systematic interventions that support more positive views of aging at the individual and societal levels.